ACCEPTANCE OF PARENTS TOWARD AUTISM KID AND THEIR ROLE IN AUTISM THERAPY - Sri Rachmayanti; Anita Zulkaida (Universitas Gunadarma, 2008)
The aim of this study is to gain a comprehensive description about the acceptance of parents with autism children and their role in austism therapy. The approach of this study is a qualitative study with interview and observation as tools of research. The participants of this study are three parents with autism children. The result shows that all the participants already accepted the fact that their children has autism. Factors influencing the acceptance are support from the big family, finacial factor, religion background, educational level, marital status age and support from expert and the society. All the participants have significant role in handling their children from make sure for the diagnose, looking for good doctor and also build good communication with the doctor, etc.Key words: parents acceptance, autism children, parents role in therapy